Epstein–Barr virus and regulatory T cells in Egyptian paediatric patients with acute B lymphoblastic leukaemia - Ateyah, Mohamed E; Hashem, Mona E; Abdelsalam, Mohamed (Journal of clinical pathology, 2017)
ObjectiveAcute B lymphoblastic leukaemia (B-ALL) is the most common type of childhood malignancy worldwide but little is known of its origin. Recently, many studies showed both a high incidence of Epstein–Barr virus (EBV) infection and high levels of CD4+CD25+Foxp3+(Treg cells) in children with B-ALL. In our study, we investigated the possible relationship between EBV infection and the onset of B-ALL, and its relation to expression of CD4+, CD25high+Foxp3+ T regulatory cells.Subject and methodsWe analysed expression and mean fluorescence intensity (MFI) of Treg cells in peripheral blood of 45 children with B-ALL and in 40 apparently healthy children as a control, using flow cytometry. Serum anti-EBV viral capsid antigen (VCA) IgG, anti-EBV nuclear antigen (EBNA) IgG (for latent infection) and anti-EBV VCA IgM (for acute infection) were investigated using ELISA.ResultsAnalysis of the Treg cells population in patients and controls revealed that expression of CD4+ CD25high+ T lymphocytes was higher in patients than in controls (mean±SD 15.7±4.1 and 10.61±2.6 in patients and controls, respectively, and MFI of Foxp3 was 30.1±7.1 and 16.7±3.7 in patients and controls, respectively (p<0.001)). There was a high incidence of latent EBV infection in patients (31%) compared with controls (10%) while the incidence of acute infection was 12% in patients and 0% in the control group. To study the role of latent EBV infection in the pathogenesis of acute B-ALL, OR was calculated (OR=4.06, coefficient index 1.2–13.6).ConclusionsThese findings suggest a possible role for Treg cells and EBV in the pathogenesis of B-ALL. Further studies are needed on the possible mechanisms of tumour genesis related to Treg cells and EBV in children with B-ALL.